The Effect of Celebrity Endorsers, Service Features, and Promotions for Shopee E-marketplace Purchase Interest - Nasiska Maria Ulfa; Abdurrahman Faris Indriya Himawan (Indonesian Vocational Research Journal, 2022)
Digitization will continue to occur so that the digital economy will later become the main pillar of the economy in Indonesia. The rapid growth of e-marketplaces in Indonesia is expected to spur entrepreneurs to be more innovative. This certainly opens up opportunities for micro and macro economic actors to start businesses more easily. The e-marketplace that has proven its rapid development is Shopee, where Shopee ranks first in the e-marketplace with the most visits. This study aims to test the implementation of the influence of celebrity endorsers, service features, and promotions on shopee e-marketplace buying interest. . This study uses a quantitative approach, with the SPSS 20 research method. In this study, the population is the 2018 Muhammadiyah University of Gresik management study program using 137 samples obtained from students who are interested in buying at the e-marketplace shopee. The test was carried out using multiple linear regression. The regression results show that celebrity endorsers affect buying interest, service features affect buying interest, and promotions affect buying interest. This study has limitations when distributing questionnaires to several respondents.